Impact of BRICS? investment in vaccine development on the global vaccine market - Miloud Kaddar; Julie Milstien; Sarah Schmitt (The World Health Organization, 2014)
Brazil, the Russian Federation, India, China and South Africa - the countries known as BRICS - have made considerable progress in vaccine production, regulation and development over the past 20 years. In 1993, all five countries were producing vaccines but the processes used were outdated and non-standardized, there was little relevant research and there was negligible international recognition of the products. By 2014, all five countries had strong initiatives for the development of vaccine technology and had greatly improved their national regulatory capacity. South Africa was then the only BRICS country that was not completely producing vaccines. South Africa is now in the process of re-establishing its own vaccine production and passing beyond the stage of simply importing, formulating and filling vaccine bulks. Changes in the public sector's price per dose of selected vaccines, the global market share represented by products from specific manufacturers, and the attractiveness, for multinational companies, of partnership and investment opportunities in BRICS companies have all been analysed. The results indicate that the BRICS countries have had a major impact on vaccine price and availability, with much of that impact attributable to the output of Indian vaccine manufacturers. China is expected to have a greater impact soon, given the anticipated development of Chinese vaccine manufacturers in the near future. BRICS' accomplishments in the field of vaccine development are expected to reshape the global vaccine market and accelerate access to vaccines in the developing world. The challenge is to turn these expectations into strategic actions and practical outcomes.